Comparison of Bio-C Pulpo and MTA Repair HP with White MTA: effect on liver parameters and evaluation of biocompatibility and bioactivity in rats - Delfino, Mateus Machado [UNESP]; de Abreu Jampani, José Leandro [UNESP]; Lopes, Camila Soares [UNESP]; Guerreiro-Tanomaru, Juliane M. [UNESP]; Tanomaru-Filho, Mário [UNESP]; Sasso-Cerri, Estela [UNESP]; Cerri, Paulo S. [UNESP] (Wiley, 2021)
Aim: To evaluate the tissue response promoted by Bio-C Pulpo (Bio), MTA Repair HP (MTA-HP) and White MTA (WMTA) and whether these materials cause liver changes in a rat experimental model. Methodology: Polyethylene tubes filled with Bio, MTA-HP and WMTA, and empty tubes (control group, CG) were implanted into the subcutaneous tissues of rats for 7, 15, 30 and 60 days. Inflammatory reaction score (IRS), capsule thickness, number of inflammatory cells (IC), von Kossa reaction, interleukin-6 (IL-6) and alkaline phosphatase (ALP) immunohistochemistry reactions were performed. Combined methods, von Kossa followed by immunohistochemistry for detection of ALP, were performed. At 60 days, the serum glutamic-oxaloacetic transaminase (GOT) and glutamic-pyruvic transaminase (GPT) levels were measured and liver fragments were collected for histological analysis; the data were assessed by one-way ANOVA analysis followed by Sidak's post-test. The biocompatibility and bioactivity data were subjected to the two-way ANOVA analysis followed by Tukey post hoc test, except the IRS. The IRS data were subjected to the Kruskal–Wallis ANOVA non-parametric test followed by Dunn's test (p ≤.05). Results: No significant difference was detected in serum GOT and GPT concentrations and in the number of hepatocytes among the experimental and CG samples. Although Bio-C Pulpo had the highest IC and IL-6-immunolabelled cells (p < 0.0001) at all periods, no significant difference was observed in the IRS among the materials, except at 60 days. In this period, the WMTA had lower IRS. All groups had a significant reduction in the capsule thickness and in the number of IC and IL-6-immunolabelled cells over time. Bio-C Pulpo, MTA-HP and WMTA specimens had greater immunoexpression of ALP than CG (p <.0001). At all periods, von Kossa-positive and birefringent structures were observed in the capsules around the materials. ALP-immunolabelled cells were also seen near von Kossa-positive structures. Conclusions: Bio-C Pulpo, MTA-HP and WMTA materials did not cause morphological changes in the liver and no significant alteration in the serum GOT and GPT levels. Moreover, these bioceramic materials were biocompatible and exhibited bioactive potential. However, Bio-C Pulpo induced greater inflammatory infiltrate than MTA-HP and WMTA at all periods.
Keywords: bioactivity; biocompatibility; immunohistochemistry; inflammatory infiltrate; interleukin-6; liver; systemic effect